Pengaruh Pembelajaran Kooperatif Tipe Student Team’s Achievement Division (STAD) terhadap Hasil Belajar Fiqih Siswa Kelas VII MTS Masmur Pekanbaru - Riki Sutiono (STAIN Bengkalis, 2021)
This study aims to determine whether or not there is a significant effect of Student Team's Achievement Division (STAD) Cooperative Learning on students' fiqh learning outcomes. The form of this research is Quasi Experiment with a Posttest-only Design with a Nonequivalent Group. The subjects studied were 75 students of class VII MTs Masmur Pekanbaru, while the object of the study was the result of learning fiqh. Data retrieval using documentation techniques, tests, and observations is carried out every meeting. The action was carried out six times, namely four meetings using the Student Team's Achievement Division (STAD) Cooperative Learning Type, one post-test meeting, and one practical exam meeting. Research data were analyzed using the t-test formula. The results showed that the Student Team's Achievement Division (STAD) Cooperative Learning had a significant effect on fiqh learning outcomes.